EFFECT OF TRACE METAL FECL3 ON BIOGAS PRODUCTION IN INDUSTRIAL WASTEWATER TREATMENT WITH HIGH ORGANIC LOAD - Yanqoritha, Nyimas; Kuswandi, Kuswandi (International Journal of Mechanical Engineering Technologies and Applications, 2023)
Wastewater from the food industry that contains a high organic load, such as wastewater from the tofu manufacturing process, requires an appropriate and efficient treatment system to reduce pollutants before being discharged into water bodies. The most suitable treatment for high organic loads is the anaerobic treatment system. The anaerobic treatment process is a system of suspended media, attached media, or the combination thereof as a hybrid. This study uses a Hybrid Upflow Anaerobic Sludge Blanket (HUASB) reactor with the consideration that this reactor has advantages in maintaining high concentrations of biomass, high operating load rates, good decomposition capabilities, and good solid-liquid separation due to suitable granulation. The purpose of this study was to determine the effect of the addition of the trace metal FeCl3 on biogas production and the ability to remove pollutants in the tofu industrial process wastewater treatment in the HUASB reactor. The operation of the reactor uses variations in the concentration of tofu industrial waste water (75 and 100%) and trace metal concentrations (0.3–0.6 mg/L). The optimum biogas production was obtained with 8190 mL at a concentration of 75% tofu industrial waste water, a trace metal concentration of 0.6 mg/L FeCl3, and removal of COD and TSS of 94.09% and 94.2%, respectively. The role of the trace metal FeCl3in the anaerobic process shows that it is a source of nutrition for increasing the growth of microorganisms in anaerobic systems so that biogas production and pollutant removal are increased.